Penggunaan Mucuna bracteata pada Berbagai Kemiringan Lahan Kelapa Sawit TBM-III dalam Rangka Perbaikan Sifat Fisik Tanah - Sari, Sanda Ratna; Wawan, Wawan; Idwar, Idwar (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
The purpose of this study was to determine the effect using LCC Mucuna bracteata at various land slope of palm TBM-III on soil physical properties and plant root growth of palm oil. This research has been conducted in PTPN V Unit Lubuk Dalam, Siak and the analysis of soil physical properties at Soil Laboratory, Faculty of Agriculture, University of Riau. This study lasted from January to April 2016. The research was conducted by using split plot design. The level of land slope (K) as the main plot which are: K1 = land slope 0% - 3%, K2 = land slope >3% - 8%, K3 = land slope >8% - 15%. The using LCC Mucuna bracteata (M) as the subplot, which are: M0 = land planted with oil palm without LCC Mucuna bracteata, M1 = land planted with oil palm LCC Mucuna bracteata. Parameters observed are water content airy, soil temperature, bulk density, particle density, total of pore space, permeability, soil organic matter, root dry weight, root volume and root occupy. The results showed: (1) the interaction of land slope and the using LCC Mucuna bracteata does not affect all of the soil physical properties and the root growth of oil palm plantations, except for water content airy in the soil depth 20-30 cm; (2) the land slope only affects the water content airy in the soil depth 0-10 cm; and (3) the using LCC Mucuna bracteata effect on water content airy, bulk density, particle density, total pore space in the soil depth of 0-5 cm, permeability and soil organic matter.Â Keywords: Mucuna bracteata, land slope, soil physical propertiesÂ